Influence of dietary supplementation on serum vitamin A and D concentrations and their seasonal variation in horses - Saastamoinen, Markku; Juusela, Johanna (Agricultural Research Centre of Finland, The Scientific Agricultural Society of Finland, The Finnish Society of Dairy Science, 1992)
Neljälläkymmenellä täysikasvuisella ravi- ja ratsuhevosella tutkittiin ruokinnan vitamiinitäydennyksen vaikutusta seerumin A (retinoli)- ja D(25(OH)D)-vitamiinitasoihin eri vuodenaikoina. Vitamiinitäydennys aloitettiin sisäruokintakauden alussa tai keskivaiheilla. Täydennys kesti siten joko syyskuun tai tammikuun alusta toukokuun loppuun. Suun kautta annetulla vitamiinilisällä tai laidunkauden pituudella ei ollut johdonmukaista vaikutusta seerumin vitamiinitasoihin. Myöskään johdonmukaista vuodenajasta johtuvaa vaihtelua seerumin A- ja D vitamiinitasoissa ei todettu.

An experiment involving 40 adult trotters and saddle horses was conducted during a period of one year in order to investigate the influence of vitamin A (retinol) and D (25-(OH)D) supplementation on serum vitamin concentrations and the seasonal variation of the serum concentrations of these vitamins. Vitamin supplementation was started either at the beginning or in the middle of the indoor (winter) feeding period. Supplementation lasted from the beginning of September or January to the end of May. According to the results, neither the dietary vitamin supplementation nor the length of the grazing period had any consistent effect on the serum vitamin concentrations. Neither was there any systematic seasonal variation in the serum retinol and 25-hydroxyvitamin D levels.
Keywords: hevonen; ruokinta; seerumi; vitamiinit; blood serum; equine; fat-soluble vitamins